The effect of numbered heads together (NHT) and problem cards on 10th-grade students’ collaboration and communication skills - Herlina, Vita; Setyawati, Siti Mukhlishoh; Lestariyanti, Elina (Proceedings of International Conference on Research in Education, 2025)
This study aimed to determine the effect of the Numbered Heads Together (NHT)-type cooperative learning model assisted by Problem Card media on the collaboration and communication skills of class X students of SMA Negeri 10 Semarang. The type of research used is a quasi-experimental with a Posttest-Only Control Group Design. The research sample consisted of students in classes X-9 (control class) and X-10 (experimental class), each totaling 35 students. Data were collected using an observation sheet and a questionnaire. Data analysis used the Independent Sample t-Test. The results obtained were an Asymp. Sig. (2-tailed) value on the observation sheets and questionnaires of 0.000 < 0.05. Therefore, Ha is accepted, which indicates that the NHT type cooperative learning model assisted by Problem Card media has an effect on the collaboration and communication skills of class X students in biology learning at SMA Negeri 10 Semarang. Further researchers can examine the comparative effectiveness of the NHT learning model assisted by problem cards with other cooperative models on students’ collaboration and communication skills in other materials or lessons.